Kinetic investigation for in-situ epoxidation of unsaturated fatty acid based on the Pseudo-steady-state-hypothesis (PSSH) - Sawitri, Dyah Retno; Mulyono, Panut; Rochmadi, .; Anwaruddin, Hisyam; Arief, Budiman (Japan Oil Chemists Society, 2020)
Oleic acid is a mono-unsaturated fatty acid that can be found abundantly in various vegetable oils and potentially attractive to be used as raw material for epoxide chemical. In-situ epoxidation of oleic acid was conducted in batch reactor using peroxy-formic at 30-60℃. Pseudo-steady-state-hypothesis (PSSH) was applied to develop the kinetic model. Heterogeneous liquid-liquid system was chosen and four models which emphasized on the ring opening agent (ROA) and reversibility of the epoxidation reaction were proposed. It has been suggested that reversible model is well suited to represent the experimental data. Activation energy obtained from Arrhenius equation is in the range of 40-195 kJ/mol.